Motorcycle Credit Purchase Decision Support System With Additive Ratio Assesstment (ARAS) Method - Jecika Azzahra; Yani Maulita; Milli Alfhi Syari (International Journal of Health Engineering and Technology, 2022)
In the era of globalization as it is today, life is felt to be growing rapidly, the number of people's needs for private vehicles to facilitate all daily activities. The development of increasingly advanced technology makes us to know the importance of the use of computers in the process of processing data quickly and practically. CV. Aneka Teknik is a company engaged in motorcycle sales services by way of cash and credit. This company cooperates with several Leasing. So far, the company only accepts application files from consumers without testing files from consumers whether they deserve credit or not.  This makes leasing difficult to handle so that the process of granting credit becomes slow. To overcome this, the author makes an application for a decision support system in determining the application of prospective customers to obtain credit facilities. After CV. Aneka Teknik processes incoming consumer files, so the files that are eligible to get credit are sent or submitted to leasing. The highest score in the ranking obtained by the ARAS method decision support system in the highest position is A9 with the name Apriandi Alfa Reza Saragih with a value of 0.1538 who has the right to be selected as a motorcycle loan recipient